Perbedaan Kebocoran Mikro komposit Nanohybrid Pasca Aplikasi Etsa Asam Tartarat Antara Konsentrasi 10%, 35%, dan 40 - Luqman Mahadika Cahyono; Irfan Dwiandhono; Ryana Budi Purnama; Rinawati Satrio; Pratiwi Nur Widyaningsih (Jurnal Material Kedokteran Gigi, 2021)
Composite resin is the material most often used as a restorative material. Acid etching is one of the procedures to help provide a place for penetration of bonding materials and composite resins. The acidic etching material that is often used is 37% phosphoric acid, but 37% phosphoric acid can cause inflammatory cell infiltration. Tartaric acid composed of weak acids that has potential to be an alternative acid etching. The aim of this study is to determine whether there are differences in microleakage of nanohybrid composites after application of tartaric acid etching between concentrations of 10%, 35%, and 40% in prevention of microleakage. This research is a laboratory experimental research with a posttest-only group design. Research samples are 24 maxillary first premolar were divided in 4 groups. Group I with 10% tartaric acid, group II with 35% tartaric acid, group III with 40% tartaric acid and group IV with 37% phosphoric acid etching. Based on the results of the LSD test it shows that There is microleakage of nanohybrid composites after etching application of tartaric acid concentrations of 10%, 35%, 40%, and 37% phosphate in class I cavities. Tartaric acid concentration of 40% can be used as an alternative to etching 37% phosphoric acid in preventing microleakage.